Type and Accuracy of Dental Implant Surgical Guide - Adam, Loot; Yossoontorn, Kanjana; Choengprapakorn, Dheeratt; Limmonthol, Saowaluck (Khon Kaen University Dental Journal, 2024)
At present, there are various techniques for implant placement, including the free hand technique and the placement by using static surgical guide and dynamic surgical guide. Each technique has different steps and methods that lead to different results and accuracies. This article aims to provide information about the types of surgical guides and the accuracy of dental implant placement using various techniques. This article compiles and compares the studies which related to the accuracy of implant placement using different techniques to provide the guidelines for choosing the appropriate surgical guide in implant placement.